Strategies for business sustainability in a collaborative economy - Leon, Ramona-Diana, 1986- (Practice, progress, and proficiency in sustainability (PPPS) book series., 2020)
"This book focuses on organizational tools and practices that may foster a company's success in the new economic context, which is defined by the faster pace of technological progress and the entrance of Generation Z on the labor market"--